Real Estate Refinancing - Nasser Abdullah Ayed Al-Qahtani (International Journal of Law Research and Studies, 2025)
This research deals with real estate refinancing as one of the important financial tools to support the real estate finance sector in the Kingdom of Saudi Arabia, highlighting its vital role in enhancing the stability of this sector and supporting the financial liquidity of financiers. This research reviews the legal and regulatory frameworks for real estate refinancing, focusing on the concept of securitization, its parties, and its historical and economic importance, in addition to analyzing the legal basis for refinancing activity in light of local laws and regulations, including the rules of the Saudi Central Bank. This research is divided into two sections, the first of which deals with securitization, and the second with real estate refinancing. The study came out with many results, the most important of which is that the Saudi legislator did not explicitly stipulate securitization in the real estate finance systems, but given that the concept of securitization as a financial tool for real estate finance is nothing but a resale of debts resulting from real estate finance operations, the legislator has authorized real estate finance companies to refinance real estate through real estate refinancing companies, and the Saudi Central Bank has set special rules for these companies to regulate them. It has also reached a number of recommendations, the most important of which is to consider the possibility of amending the real estate refinancing rules document into an executive regulation.